If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2t + 5) = 4 Reorder the terms: 6(5 + 2t) = 4 (5 * 6 + 2t * 6) = 4 (30 + 12t) = 4 Solving 30 + 12t = 4 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 12t = 4 + -30 Combine like terms: 30 + -30 = 0 0 + 12t = 4 + -30 12t = 4 + -30 Combine like terms: 4 + -30 = -26 12t = -26 Divide each side by '12'. t = -2.166666667 Simplifying t = -2.166666667
| -45=-6(-36-4) | | 7n^2-52n-32=0 | | x^2-x=552 | | 20+x=2(20+x) | | (3p-4)=35 | | 2(x-5)+3(2x-8)= | | 16=8 | | 6x+24=4.7 | | 9x^2-5x= | | 16=0.5r | | x*3-6=x*12-177 | | 27y^7+24y^4=0 | | x^2-x=462 | | 4x^2-6x-10=00 | | 3c+9=6(1c+9) | | 2x+37=4x-9 | | n=-120 | | 0.66+2y=4y-0.13 | | -6x-10=2+14 | | 5(12+4)=8x | | 490=-7n | | x^2+34x+11=0 | | 3x+24=38 | | 42=14n | | X+4y=1 | | 157-2x=34x+23 | | -21.536=1.6(9-m) | | x+x+1+x+4=-18 | | x*.5+2=0.33 | | 18x=180 | | x^3-2x^2-47x-6=0 | | 17-x=28-2x |